Therapeutic strategies targeting folate receptor α for ovarian cancer - Mai, Jia; Wu, Limei; Yang, Ling; Sun, Ting; Liu, Xiaojuan; Yin, Rutie; Jiang, Yongmei; Li, Jinke; Li, Qintong (Frontiers in Immunology, 2023)
Epithelial ovarian cancer (EOC) is the deadliest gynecological cancer, and presents a major clinical challenge due to limited treatment options. Folate receptor alpha (FRα), encoded by the FOLR1 gene, is an attractive therapeutically target due to its prevalent and high expression in EOC cells. Recent basic and translational studies have explored several modalities, such as antibody-drug conjugate (ADC), monoclonal antibodies, small molecules, and folate-drug conjugate, to exploit FRα for EOC treatment. In this review, we summarize the function of FRα, and clinical efficacies of various FRα-based therapeutics. We highlight mirvetuximab soravtansine (MIRV), or Elahere (ImmunoGen), the first FRα-targeting ADC approved by the FDA to treat platinum-resistant ovarian cancer. We discuss potential mechanisms and management of ocular adverse events associated with MIRV administration.